PENDEKATAN HUKUM KESEHATAN YANG SENSITIF BUDAYA DALAM MEMBANGUN KEPERCAYAAN ANTARA PASIEN DAN TENAGA MEDIS UNTUK MENINGKATKAN EFEKTIVITAS PELAYANAN DAN MENGURANGI KONFLIK DI INDONESIA: KAJIAN PUSTAKA - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study examines culturally sensitive approaches to health law in building trust between patients and medical personnel as a means of improving service effectiveness and reducing conflict in Indonesia. Given Indonesia's highly diverse cultural background, a purely normative approach to law that does not take cultural values into account often presents obstacles to health services. This literature review examines various health regulations, legal principles, and literature related to cultural sensitivity and how its application can strengthen communication, trust, and cooperation between patients and medical personnel. The results of the study show that the integration of culture into health law policies and practices is essential to creating inclusive, humane, and equitable services. This approach also plays a role in reducing disputes and conflicts that arise due to differences in cultural values in healthcare services.